O significado da nutrição parenteral para o cliente no contexto hospitalar - Freitas, Consuelo Helena Aires de (1995)
The initiative to understand the meaning of Parenteral Nutrition towards the client in the hospital context carne from my personal questioning about Nursing Care. I intended to comprehend better the feelings and behaviours of our clients, family participation and different interpretations, that make Parenteral Nutrition a way to treat diseases. Participative observations were made, as well interviews and diligences with seven clients in the hospital, who were taking Parenteral Nutrition. The goal of these investigation was centred in the following question: How do you feel taking Parenteral Nutrition? The sentiment of being hospitalized was also investigated. All the informations we got were put together into two themes: the social, economical and cultural context, besides the idea of facing patienfs situaíion. These informations were analysed in an interactive approach, showing the situaíion faced by the paíients, who have hospital assistance; how they fell Parenteral Nutrition within this context; and what meanings were given to it. This study revealed the feelings, behaviours, and altitudes related to the biological, emotional and social-cultural aspects of the paiient, all of them were linked to Parenteral Nutrition; the limits faced by Parenteral Nutrition and its obstacles in the nursing assistance were understood from the social interaction between the patient and his nursing group, making evident all the client and his/her family's interpretations.